2021
DOI: 10.1021/acs.jpcc.1c05376
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Green Synthesis of a PEO/TCPP/LiClO4 Solid Polymer Electrolyte with Improvement of Ion Transport

Abstract: All-solid-state Li-ion batteries (ASSBs) composed of safe and reliable solid electrolyte materials have become increasingly important in energy storage systems. Poly(ethylene oxide) (PEO)-based electrolytes have been rapidly developed for ASSBs over recent years due to their nonflammability, shape flexibility, good interface contact with electrodes, and better electrochemical stability. Nevertheless, their low ionic conductivity remains a serious issue to be addressed urgently. Herein, we report a solid compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Polymer crystallinity is analyzed based on the two primary peaks at 19 and 23° exhibited by pure PEO. The peak at 19° is indexed to the [120] crystal plane, and that at 23° is attributed to the [032] crystal plane. Changes in peak intensity, peak position, and peak width are direct manifestations of changes in PEO crystallinity caused by the PEO–salt interaction and/or PEO–h-BN interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer crystallinity is analyzed based on the two primary peaks at 19 and 23° exhibited by pure PEO. The peak at 19° is indexed to the [120] crystal plane, and that at 23° is attributed to the [032] crystal plane. Changes in peak intensity, peak position, and peak width are direct manifestations of changes in PEO crystallinity caused by the PEO–salt interaction and/or PEO–h-BN interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers dope the PEO/ PEG electrolyte into the channels of COFs to utilize the potential synergy of PEG-based and COF-based solid electrolytes. 19,20 For instance, Cheng et al 21 developed a novel solid electrolyte (TPBD-LiPF 6 @PEO) with a high ionic conductivity of 0.543 mS cm −1 at 25 °C and demonstrated that the strong interaction between TPBD of a -CvO peak and Li + promotes LiPF 6 dissociation. Wang et al 22 proposed a strategy to incorporate lowmolecular-weight polyethylene glycol (PEG) into COFs with anionic, neutral, or cationic skeletons to accelerate Li + conduction and the ion conductivity of PEG including a cationic COF can reach 1.78 × 10 −3 S cm −1 at 120 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Further, different covalent organic polymers with ionic functionality or capable of hydrogen bonding with the PEO chains were also dispersed as fillers into the PEO matrix where the improved electrochemical performances were ascribed to the suppressed crystallization of the PEO domains. 33,34 Based on the above considerations, herein, a unique organic polymer framework (OPF) was synthesized by the Suzuki− Miyaura coupling reaction between 2,5-dibromo-3-(2-(2-(2ethoxyethoxy)ethoxy)ethyl)thiophene and triazine-phenyl boronic acid. Such organic covalent frameworks without long side chains on their backbone are generally crystalline in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these reports are focused on anchoring PEG groups to the organic frameworks and evaluating their performance as solid electrolytes as such at high temperatures. Further, different covalent organic polymers with ionic functionality or capable of hydrogen bonding with the PEO chains were also dispersed as fillers into the PEO matrix where the improved electrochemical performances were ascribed to the suppressed crystallization of the PEO domains. , …”
Section: Introductionmentioning
confidence: 99%